An experimental approach to explain the southern Andes elevational treeline1. Issue 5 (1st May 2014) - Fajardo, Alex; Piper, Frida I.
Abstract : Premise of the study: The growth limitation hypothesis (GLH) is the most accepted mechanistic explanation for treeline formation, although it is still uncertain whether it applies across taxa. The successful establishment of Pinus contorta ––an exotic conifer species in the southern hemisphere––above the Nothofagus treeline in New Zealand may suggest a different mechanism. We tested the GLH in Nothofagus pumilio and Pinus contorta by comparing seedling performance and carbon (C) balance in response to low temperatures. Methods: At a southern Chilean treeline, we grew seedlings of both species 2 m above ground level, to simulate coupling between temperatures at the meristem and in the air (colder), and at ground level, i.e., decoupling air temperature (relatively milder). We recorded soil and air temperatures as well. After 3 yr, we measured seedling survival and biomass (as a surrogate of growth) and determined nonstructural carbohydrates (NSC). Key results: Nothofagus and Pinus did not differ in survival, which, as a whole, was higher at ground level than at the 2‐m height. The root‐zone temperature for the growing season was 6.6°C. While biomass and NSC decreased significantly for Nothofagus at the 2‐m height compared with ground level (C limitation), these trends were not significant for Pinus . Conclusions: The treeline for Nothofagus pumilio is located at an isotherm that fully matches global patterns; however, its physiological responses to low temperatures differed from those of other treeline species. Support for C limitation in N. pumilio but not in P. contorta indicates that the physiological mechanism explaining their survival and growth at treeline may be taxon‐dependent.